(untitled) (Mongolian Journal of Agricultural Sciences, 2018)
The paper addresses planning issues of hay land based on new methods of suitability and need’s assessment of local area. In order to develop the hay land future use and planning for 2023 of Erdenetsagaan soum, Sukhbaatar aimag, the assessment of the haymaking situation, the number of livestock growth and needs of nutritional resources for animal husbandry were calculated. According to the tested new suitability assessment of hay land, 4.37 percent or 74164 ha of land are most suitable, and 29.21 percent or 496014.3 ha are unsuitable. In order to calculate the nutritional needs of livestock in the future, the demand of green fodder for hay cut is estimated at 6712 t in 2023. The need for this fodder supply requires 8391 ha hay fields in 2023. Thus, demand (6712 t hay from 8391 ha of field) of green fodder will be supplied after proper implementation of plan (74164 ha suitable field to hay land usage).